A proteomic view on the differential phenotype of Schwann cells derived from mouse sensory and motor nerves. Issue 6 (13th September 2020) - Shen, Mi; Tang, Wei; Cheng, Zhenghui; Zhang, Qi; Chen, Zixin; Tian, Yingchao; Zhang, Yawen; He, Qianru; Shi, Haiyan; Zhu, Hui; Wu, Han; Ji, Yuhua; et al.
Abstract: Schwann cells (SCs) are myelin‐forming glial cells of the peripheral nervous system. Recent studies suggested that SCs comprise two phenotypes: sensory SCs and motor SCs, which are associated with the modality‐specific promotion of sensory and motor axon growth during peripheral neuronal regeneration. However, the molecular basis of the two phenotypic SCs is unclear. We established a workflow to obtain highly purified SCs derived from sensory nerve (SNdSCs) and motor nerve (MNdSCs) from B6; D2‐Tg(s100B‐EGFP)1Wjt/J mice. Subsequently, a quantitative proteomic analysis based on iTRAQ labeling was performed to compare the proteome of SNdSCs and MNdSCs. A total of 6, 567 proteins were identified, of which 63 and 11 proteins were overexpressed in SNdSCs and MNdSCs, respectively. Three of the overexpressed proteins were further validated by western blot and immunocytochemistry: GMFB and CNPase, which were overexpressed in sensory SNdSCs, and histone H4, which was overexpressed in MNdSCs. The expression pattern of the three proteins was also validated in the dorsal roots and ventral roots. Bioinformatics analysis indicated that proteins highly expressed in SNdSCs are mainly involved in RNA processing and protein synthesis, while those overexpressed in MNdSCs are related to cell proliferation. Real‐time cell analysis confirmed that the proliferation activity of MNdSCs is higher than that of SNdSCs. This study is the first to provide a proteomic view of the differential phenotype of mouse SNdSCs and MNdSCs. The data may serve as a valuable source for the study of the biological characteristics of these two SC phenotypes and their roles in nerve‐specific regeneration. Abstract : Schwann cells (SCs) were found to have sensory and motor phenotypes and associated with the modality specific promotion of sensory and motor nerve regeneration. To explore the differences between them, we established a workflow to obtain highly purified SCs derived from sensory nerve (SNdSCs) and motor nerve (MNdSCs) from B6; D2‐Tg(s100B‐EGFP)1Wjt/J mice. The SNdSCs and MNdSCs were isolated from dorsal and ventral roots by FACS sorting. The proteome of SNdSCs and MNdSCs was compared by a quantitative proteomic analysis based on iTRAQ labeling and the mouse Schwann proteome was obtained. Several differentially expressed proteins between SNdSCs and MNdSCs were verified.